Role of phytochemicals in combating corona - virus infection: A review - Md. Mukhtar AHMED; Anjali RAWANI; Arpita GOPE; Jayeeta KHANRAH (Notulae Scientia Biologicae)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome corona virus-2 (SARS-COV-2), is the most important health issue, all over the world. Few successful vaccines have been approved till now against SARS-COV-2. Phytochemicals, also called phytonutrients are compounds in plant foods that can be helpful in various chronic diseases. It brings hope for human health during this pandemic, and a great deal of research is concentrated on it. Phytochemicals have been used as antiviral agents against several viruses via different mechanisms of direct inhibition either at the viral entry point or the replication stages and via immunomodulation potentials. The last three years are evidence of detailed and focused investigations on the biologically active constituents derived from medicinal plants against SARS-CoV-2. The curious and outstanding results of these investigations have emerged the medical and plant experts in pharmacognosy (study of medicinal plants and other natural substances sources of drugs) enough to regard as herbal medicines and plant-based products as they are more effective in combating the COVID-19 crisis. This review discusses the potential of medicinal plants and herbal compounds for treating COVID-19 in the present and the future. These compounds are a natural and sustainable alternative for the treatment of COVID-19. The current article evaluates the various strong evidences from biochemical and molecular studies that have been investigated so far for the development of herbal formulations to combat COVID-19 with detailed focus on the most potential phytochemicals of medicinal plants studied in this regard namely, Withania somnifera, Cinchona officinalis, Curcuma longa, Ocimum sanctum, Azadirachta indica and Tinospora cordifolia.